Fe3O4@Pt nanoparticles to enable combinational electrodynamic/chemodynamic therapy - Tong Chen; Qiang Chu; Mengyang Li; Gaorong Han; Xiang Li (Journal of Nanobiotechnology, 2021)
Abstract Electrodynamic therapy (EDT) has recently emerged as a potential external field responsive approach for tumor treatment. While it presents a number of clear superiorities, EDT inherits the intrinsic challenges of current reactive oxygen species (ROS) based therapeutic treatments owing to the complex tumor microenvironment, including glutathione (GSH) overexpression, acidity and others. Herein for the first time, iron oxide nanoparticles are decorated using platinum nanocrystals (Fe3O4@Pt NPs) to integrate the current EDT with chemodynamic phenomenon and GSH depletion. Fe3O4@Pt NPs can effectively induce ROS generation based on the catalytic reaction on the surface of Pt nanoparticles triggered by electric field (E), and meanwhile it may catalyze intracellular H2O2 into ROS via Fenton reaction. In addition, Fe3+ ions released from Fe3O4@Pt NPs under the acidic condition in tumor cells consume GSH in a rapid fashion, inhibiting ROS clearance to enhance its antitumor efficacy. As a result, considerable in vitro and in vivo tumor inhibition phenomena are observed. This study has demonstrated an alternative concept of combinational therapeutic modality with superior efficacy.